Heart rate profile during prolonged high intensity cycling at low and moderate altitudes - Anholm, J. D.; Bonjour, S.; Brayley, K.; Blackburn, R.; Conde, J.; Eichman, W.; Sanders, K.; Hughes, W.; Pettis, J. L. (Medicine & Science in Sports & Exercise, 1995)
During prolonged constant work-load exercise, heart rate increases along with a decrease in stroke-volume changes and is collectively referred to as "cardiovascular drift." Trained cyclists (N = 20) performed flat and hilly terrain rides at sea-level (450 m) and altitude (2150-3120 m). It was found that the heart rate response to 3-5 hours of intense exercise at altitude differed from the cardiovascular drift response observed at sea-level. Implication: The cardiovascular response to prolonged aerobic tasks of trained cyclists is different at altitude than it is at sea-level. This supports the concept of acclimatization specificity.